IMPLEMENTASI DIVERSI BAGI ANAK DIBAWAH UMUR YANG MELAKUKAN TINDAK PIDANA BERDASARKAN KETENTUAN UNDANG-UNDANG NOMOR 11 TAHUN 2021 TENTANG SISTEM PERADILAN ANAK - Zainal, Muhammad (JUSTNESS - Jurnal Hukun dan Agama, 2023)
ABSTRACT This research aims to analyze the implementation of diversion for underage children who commit criminal acts in accordance with the provisions of Law Number 11 of 2021 concerning the Juvenile Justice System. Diversion is an alternative approach in handling juvenile offenders with the aim of providing a learning experience without going through formal court proceedings. This study examines the process of implementing diversion, influencing factors, and the impact of using diversion on underage juvenile offenders. The research method employed in this study is a normative juridical approach. The normative juridical approach involves studying theories and concepts related to normative issues through literature review by examining existing legal materials. Furthermore, this research also utilizes a statute approach, which involves analyzing regulations and rules related to the legal issue, especially Law Number 11 of 2021. The research findings indicate that the implementation of diversion has progressed, but still faces various challenges such as diverse understandings from those involved in the juvenile justice system and the community, as well as resource limitations. These outcomes are influenced by factors such as awareness of the importance of rehabilitating children, community involvement, and coordination among relevant institutions, which significantly impact the success of diversion implementation. In the long term, diversion is expected to contribute positively to improving the behavior of juvenile offenders, reducing recidivism rates, and minimizing the negative impact of the criminal justice system on underage children. This study provides in-depth insights into the implementation of diversion for underage children involved in criminal acts or commonly known as children in conflict with the law, focusing on legal, social, and rehabilitative aspects. The implications of this research are expected to support efforts to improve the juvenile justice system and provide guidance for stakeholders to take effective steps in facilitating diversion as a viable alternative in addressing juvenile offenders.